Prevalence and Severity of Temporomandibular Disorders Among Dental Patients in Nepal: A Cross-Sectional Study Using DC/TMD and Fonseca Index - Poudel, Pragya; Nyachhyon, Rinky; Raina, Shally; Khadka, Mahesh; Gyawali, Subhekshya (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Temporomandibular disorders (TMDs) are musculoskeletal and neuromuscular conditions affecting the temporomandibular joint (TMJ), masticatory muscles, and associated structures. They are a major cause of chronic facial pain, impacting oral function and quality of life. Prevalence among dental patients varies widely. Methods: A cross-sectional study was conducted among 294 dental patients. TMDs were diagnosed using the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) and severity was assessed via Fonseca’s questionnaire. Data were collected and statistical analysis was performed to assess the correlations between demographic and clinical variables and the prevalence of TMD. Results: Among 294 participants, 40 (13.6%) patients were diagnosed with TMDs among which 65% were female and 35% were male. Pain on mouth opening was the most common sign (92.5%), followed by clicking sound (72.5%). Various diagnoses included arthralgia (12.5%), arthralgia with disc displacement with reduction (15%), and arthralgia with disc displacement with reduction with intermittent locking (12.5%). No significant correlations were observed between age, gender, range of mouth opening or molar relationship and TMD prevalence or severity. Conclusions: TMDs are common among dental patients, with pain on mouth opening as the predominant clinical sign. Age, gender, range of mouth opening and molar relationships were not significantly associated with TMD occurrence and severity. Thus, routine TMD assessment in dental practice is recommended for early detection and management.